The Leadership Style Influence Employee’s Work Commitment: A Conceptual Review In Padang Terap Community College - Rahman, Reezlin; Mohd Deris, Hosni Mubarak (Advances in Social Sciences Research Journal, 2019)
This conceptual paper is to clarify the relationship between leadership style and employee’s commitment at the Padang Terap Community College. Generally, there are two factors of leadership style that underpinning for this paper, namely the flexibility and initiative that are seen to influence work commitments in this organization. The review of this paper will provide the information, suggestion decision and contribution in addressing the situation that occurred at the Community College and thus help the management’s plan for further research and appropriate changes.